2019
DOI: 10.1002/jsfa.9665
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fruit canopy position and maturity on yield determinants and chemical composition of virgin olive oil

Abstract: BACKGROUND: While both maturity and light exposure are important factors determining olive fruit physiology, the relationship between maturity, canopy position and optimal harvesting time has not been well-studied. To understand the interaction of these factors, olive fruits from upper and lower layers of the canopy were harvested from September to January. Maturity, moisture and fat content of the fruit as well as the quality and minor components of the oil extracted were measured. RESULTS:Lower light interce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
5
16
1
Order By: Relevance
“…'Cerasuola' fruit showed higher fat content at the upper than the lower canopy layers independent of planting density, whereas 'Koroneiki' fruit showed higher values in the upper layers only at HD. These observations agree with findings from previous studies showing that fruits from lower canopy positions accounted for approximately one-fourth of tree fruit production (26%) and oil yield (25.2%) [33], while fruits from the upper canopy layers showed the highest weight, ripening index, and oil content [12,26,32]. A possible explanation for a higher oil accumulation is that fruits from upper layers were more exposed to incident light which has been shown to increase the number of oil bodies inside the fruit mesocarp [39].…”
Section: Cultivarsupporting
confidence: 92%
See 2 more Smart Citations
“…'Cerasuola' fruit showed higher fat content at the upper than the lower canopy layers independent of planting density, whereas 'Koroneiki' fruit showed higher values in the upper layers only at HD. These observations agree with findings from previous studies showing that fruits from lower canopy positions accounted for approximately one-fourth of tree fruit production (26%) and oil yield (25.2%) [33], while fruits from the upper canopy layers showed the highest weight, ripening index, and oil content [12,26,32]. A possible explanation for a higher oil accumulation is that fruits from upper layers were more exposed to incident light which has been shown to increase the number of oil bodies inside the fruit mesocarp [39].…”
Section: Cultivarsupporting
confidence: 92%
“…Fruits receiving more radiation showed the highest fruit weight, mesocarp oil content, maturity index, and total polyphenols in virgin olive oil [20]. Recently a study of 'Arbequina' also found that oil extracted from the upper layers presented higher concentration of oleuropein and ligstroside aglycone [12]. These compounds, besides having high antioxidant capacity, also contribute to the bitter and pungent flavor of the oil [21].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Values were in the range 6.1–22.2 g per 100g for “Arbequina,” 8.6–21.7 g per 100g for “Arbosana,” and 7.7–24.3 g per 100g for “Koroneiki.” The low moisture content of “Koroneiki” resulted in higher oil content on a wet basis compared to “Arbequina” and “Arbosana.” While the rate of oil accumulation started to plateau in November for “Arbequina” and “Arbosana,” it continued to increase for “Koroneiki.” Fruit harvested by the beginning of December in the South of Spain, with comparable maturation indexes and moisture contents to the ones of this study, presented lower values of oil content on a wet basis in the range 20.0–21.6 g per 100g, not showing significant differences among cultivars. [ 9 ] Previously, our group had found that the maturation index did not correlate with fat accumulation in drupes from “Arbequina.” [ 22 ] Similarly, the same observation held true for “Arbosana” and “Koroneiki” as considerable differences in oil content were observed in a period where the maturation index did not change significantly, suggesting oil content as a better harvest predictor compared with the maturation index.…”
Section: Resultsmentioning
confidence: 62%
“…[9] Previously, our group had found that the maturation index did not correlate with fat accumulation in drupes from "Arbequina." [22] Similarly, the same observation held true for "Arbosana" and "Koroneiki" as considerable differences in oil content were observed in a period where the maturation index did not change significantly, suggesting oil content as a better harvest predictor compared with the maturation index.…”
Section: Olive Fruit Parametersmentioning
confidence: 58%